The Effects of Psychoeducation on the Expressed Emotion and Family Functioning of the Family Members in First-Episode Schizophrenia - KARACA, SEMRA (SPRINGER, 2017)
The aim of this study was to determine the effects of the psychoeducation received by the family members of the patients with first-episode schizophrenia on the expressed emotion (EE) and the family functioning of the family members. This study has a quasi-experimental design with a control group. The sample of the study was 60 family members (30 experimental -30 control) of the patients with first-episode schizophrenia. The experimental group received 9 weeks of psychoeducation as a group. EE and family functioning were assessed at the beginning and at the end of the psychoeducation program. EE criticism/hostility and over involvement-protecting-intervention levels of the family members have decreased at the end of the psychoeducation (p < 0.05). Family functioning has changed too at the end of the psychoeducation (p < 0.05), and assessed as more healthy. Consequently, early psychoeducational groups may be effective in decreasing EE level and improving the family functioning for a family member of patient with first-episode schizophrenia.
Keywords: Family functioning; Expressed emotion; First-episode schizophrenia; Psychoeducation; EPISODE PSYCHOSIS; 1ST EPISODE; RELATIVES; INTERVENTIONS; ATTRIBUTIONS; ASSOCIATION; OUTCOMES; PARENTS; PEOPLE; BURDEN